PERANCANGAN APLIKASI PENILAIAN SEMINAR PROPOSAL DAN SIDANG SKRIPSI DI FAKULTAS ILMU KOMPUTER UNIVERSITAS BANTEN JAYA - Yul Hendra; Ramdani Budiman; Ely Nuryani; Muharman Wahid (Jurnal Ilmiah Sains dan Teknologi, 2022)
Proposal Seminar is an activity carried out to assess the feasibility of a proposed title. To test the feasibility of this Thesis Proposal, it is tested by three examiners. So far, the process of recording the feasibility assessment of this thesis proposal is still done manually, namely by recording the value on a form. The assessment form from the three Examiners was added manually to obtain a combined score, then the faculty staff re-entered and recap manually so that this process is relatively time consuming and prone to data input errors. Thesis trial is the final testing activity of the research process that has been carried out by students through a process of guidance by two Advisory Lecturers. Similar to the proposal seminar process, the recording of the thesis trial assessment data is also still done manually, namely by recording it on the assessment form that has been provided. After the assessment data is collected, the faculty staff carry out the process of accumulating the value of the three examiners to become the final score for the trial, this process is also carried out manually so that it is prone to errors. Based on the description of the background of the problem above, we can conclude that the causes of the emergence of this research idea are: The process of inputting value data repeatedly, the first is input by the examining lecturer and the second is re-entered again by the faculty staff, The process of calculating the combined value is still done manually so it is very prone to errors, To obtain the final combined value requires a relatively long time. The methodology used for system development is the Waterfall method. The expected results are the availability of a system that is able to record the evaluation process of the proposal seminar and thesis trial so that the process of recap of combined scores is faster and the results of the proposal seminar and thesis trial results are known to students more quickly, the value data input process is not repeated for data recap and printing. reports can be faster